Immunization with Tp0954, an adhesin of Treponema pallidum, provides protective efficacy in the rabbit model of experimental syphilis - He, Yuxing; Chen, Dejun; Fu, Yue; Huo, Xinzhuo; Zhao, Feijun; Yao, Ling; Zhou, Xiuping; Qi, Pengfei; Yin, Haoquan; Cao, Longgu; Ling, Hui; Zeng, Tiebing (Frontiers in Immunology, 2023)
Syphilis, a chronic multisystemic disease caused by spirochete Treponema pallidum subspecies pallidum infection, continues to be a serious global health problem and congenital syphilis remains a major cause of adverse outcomes in pregnancy in developing countries. The development of an effective vaccine is the most cost-effective way to eliminate syphilis, but so far has been elusive. Here, we evaluated the immunogenicity and protective efficacy of Tp0954, a T. pallidum placental adhesin, as a potential vaccine candidate in a New Zealand rabbit model of experimental syphilis. Animals immunized with recombinant Tp0954 (rTp0954) produced high titers of Tp0954-specific serum IgG, high levels of IFN-γ from splenocytes and specific splenocyte proliferation response when compared to control animals immunized with PBS and Freund's adjuvant (FA). Furthermore, rTp0954 immunization significantly delayed the development of cutaneous lesions, promoted inflammatory cellular infiltration at the primary lesion sites, and inhibited T. pallidum dissemination to distal tissues or organs compared with that of the control animals. In addition, transfer of popliteal lymph nodes from Tp0954-immunized, T. pallidum-challenged rabbits to naïve rabbits failed to result in T. pallidum infection, confirming sterile immunity. These findings suggest that Tp0954 is a promising vaccine candidate against syphilis.